2021
DOI: 10.3389/fimmu.2021.648539
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophages Serve as Critical Executor of Innate Immunity in Chronic Allograft Rejection

Abstract: Allograft functional failure due to acute or chronic rejection has long been a major concern in the area of solid organ transplantation for decades. As critical component of innate immune system, the macrophages are unlikely to be exclusive for driving acute or chronic sterile inflammation against allografts. Traditionally, macrophages are classified into two types, M1 and M2 like macrophages, based on their functions. M1 macrophages are involved in acute rejection for triggering sterile inflammation thus lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Their role in kidney transplantation is still unclear. M1 macrophages could produce pro-inflammatory cytokines, which were involved in allograft rejection and result in tissue damage and poor graft survival (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their role in kidney transplantation is still unclear. M1 macrophages could produce pro-inflammatory cytokines, which were involved in allograft rejection and result in tissue damage and poor graft survival (37).…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages play important roles in anti-inflammation in allograft rejection. However, M2 macrophages are reported to contribute to fibrosis, leading to poor long-term graft survival (37). Moreover, macrophages are associated with graft vasculopathy, but the phenotypes remain unidentified (38).…”
Section: Discussionmentioning
confidence: 99%
“…While both M1 and M2 can clear dead cells, proinflammatory macrophages are crucial for clearing dead cell debris at the early stage of heart injury (14). In contrast, antiinflammatory macrophages facilitate the resolution of inflammation and boost the repairing of injured cardiac tissue (15). As a matter of fact, recent studies have revealed that proinflammatory M1-like polarization is enhanced, whereas antiinflammatory M2-like response is inhibited in diabetic hearts, resulting in cardiac inflammation and contractile dysfunction (16).…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment and surgical resection are no longer therapeutic options for many patients with end-stage and acute liver disease, and liver transplantation provides the only remaining opportunity. However, ischaemia-reperfusion injury (IRI) during surgery not only limits the utilization of many donor livers, but also severely restricts the prognosis of liver transplant patients (1)(2)(3). IRI is caused by the accumulation of inflammatory cytokines in the donor liver due to ischemia and hypoxia during perfusion Original Article Itaconic acid facilitates inflammation abatement and alleviates liver ischemia-reperfusion injury by inhibiting NF-κB/NLRP3/ caspase-1 inflammasome axis via organ preservation fluid after isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, emphasis in research on inflammatory diseases is shifting to the receding phase of inflammation. Studies have shown impaired inflammatory regression is the basis for the pathogenesis of many immune diseases and promoting regression can facilitate the restoration of immune homeostasis and mitigate the progression of inflammatory disease, providing better results than traditional "anti-inflammatory" treatment (3,9,11).…”
Section: Introductionmentioning
confidence: 99%